2020
DOI: 10.1002/jsfa.10217
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of rumen‐protected methionine decreases the nitrous oxide emissions of urine of beef cattle through decreasing urinary excretions of nitrogen and urea

Abstract: BACKGROUND: Two consecutive trials were carried out to study the effects of dietary supplementation of rumen-protected methionine (RPM) on nutrient digestibility, nitrogen (N) metabolism (Trial 1), and consequently the nitrous oxide (N 2 O) emissions from urine in beef cattle (Trial 2). Eight 24-month-old castrated Simmental bulls with liveweights of 494 ± 28 kg, and four levels of dietary supplementation of RPM at 0, 10, 20, and 30 g head −1 d −1 , were allocated in a replicated 4 × 4 Latin square for Trial 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Approaches to mitigate N 2 O emission from animal excreta include decreasing the total N excretion, regulating the fecal N-to-urinary N ratio, and supplementing tannins and tannic acids to rations ( Zhao, 2017 ; Zhao et al., 2020 ; Zhou et al, 2019 ). A recent method to mitigate the N 2 O emissions from the urine patches of grazing ruminants is to use dicyandiamide (DCD) which is an exogenous nitrification inhibitor (NI).…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to mitigate N 2 O emission from animal excreta include decreasing the total N excretion, regulating the fecal N-to-urinary N ratio, and supplementing tannins and tannic acids to rations ( Zhao, 2017 ; Zhao et al., 2020 ; Zhou et al, 2019 ). A recent method to mitigate the N 2 O emissions from the urine patches of grazing ruminants is to use dicyandiamide (DCD) which is an exogenous nitrification inhibitor (NI).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, methionine is one of the sulfur-containing amino acids, which is critical for the health, growth, and meat quality of animals [ 8 , 12 ]. Recent studies observed that dietary N utilization was improved in beef cattle as a result of the supplementation with rumen-protected methionine (RPM) [ 13 , 14 ]. Furthermore, Liu et al reported [ 15 ] that supplementation with RPL and RPM could affect rumen bacterial communities, which was positively associated with improved meat quality in yaks [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large ruminant animals have high intakes of feed and water. The efficiency of dietary nitrogen utilization of beef cattle is only about 15.9~19.0%, and although yaks have higher urea recycling and greater microbe capture of the recycled urea by the rumen than beef cattle, their dietary nitrogen efficiency still only is about 25.9%, and a large amount of nitrogen is excreted in the feces and urine [ 3 , 4 , 5 ]. In addition, the crude protein content of grass (dead matter) in the cold season is less than 5% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%